Research handbook on EU data protection law - Kosta, Eleni; Leenes, Ronald; Kamara, Irene (Research handbooks in European law series, 2022)
"Bringing together leading European scholars, this thought-provoking Research Handbook provides a state-of-the-art overview of the scope of research and current thinking in the area of European data protection. Offering critical insights on prominent strands of research, it examines key challenges and potential solutions in the field. Chapters explore the fundamental right to personal data protection, government-to-business data sharing, data protection as performance-based regulation, privacy and marketing in data-driven business models, data protection and judicial automation, and the role of consent in an algorithmic society. Expert contributors investigate the impact of Brexit on the right to data portability, essential equivalence as a benchmark for international data transfers following Schrems II, and data protection in relation to the application and boundaries of the Law Enforcement Directive, trade secret privileges, and competition law. Comprehensive, yet accessible, the Research Handbook on EU Data Protection Law will be a valuable resource for students and scholars of technology and data protection law, privacy law and European law more broadly, while also being a useful tool for practitioners and policy makers concerned with data protection"--